2006
DOI: 10.1074/jbc.m601460200
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive eIF5A Mutant Accumulates Transcripts Targeted to the Nonsense-mediated Decay Pathway

Abstract: The highly conserved protein eIF5A found in Archaea and all eukaryotes uniquely contains the posttranslationally formed amino acid hypusine. Despite being essential the functions of this protein and its modification remain unclear. To gain more insight into these functions temperature-sensitive mutants of the human EIF5A1 were characterized in the yeast Saccharomyces cerevisiae. Expression of the point mutated form V81G in a ⌬eIF5A strain of yeast led to a strongly temperature-sensitive phenotype and to a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 58 publications
1
55
0
2
Order By: Relevance
“…The GC7 treatment during the first two days of culture did not impair the process of cell differentiation possibly due to the low requirement of eIF5A during this period. The slight increase of the eIF5A transcript content during the whole period of GC7 treatment and the increase of MyoD1 transcript content in cells treated with GC7 for 48 h from the end of the second up to the end of the fourth day of differentiation may be associated to effects on mRNA stabilization as observed by others (Zuk and Jacobson, 1998;Schrader et al, 2006). However, the decline of the MyoD1 transcript content after prolongation of GC7 treatment revealed the possibility of extension of the initial phase of the differentiation program.…”
Section: Discussionmentioning
confidence: 69%
“…The GC7 treatment during the first two days of culture did not impair the process of cell differentiation possibly due to the low requirement of eIF5A during this period. The slight increase of the eIF5A transcript content during the whole period of GC7 treatment and the increase of MyoD1 transcript content in cells treated with GC7 for 48 h from the end of the second up to the end of the fourth day of differentiation may be associated to effects on mRNA stabilization as observed by others (Zuk and Jacobson, 1998;Schrader et al, 2006). However, the decline of the MyoD1 transcript content after prolongation of GC7 treatment revealed the possibility of extension of the initial phase of the differentiation program.…”
Section: Discussionmentioning
confidence: 69%
“…Supporting this notion, it has been reported that eIF5A itself has RNA-binding properties (18). Moreover, in the lower eukaryote S. cerevisiae, eIF5A appears to affect mRNA turnover/degradation (19,20), a process that is closely linked to nucleocytoplasmic mRNA transport. The present study by Maier and colleagues (3) identifies hypusine-modified eIF5A as a critical regulator of the nuclear export of Nos2 mRNA, further substantiating the notion that eIF5A has a nuclear function.…”
Section: Participation Of Eif5a In Inflammatory Responsesmentioning
confidence: 62%
“…From differential display analysis of eIF5A-associated mRNAs, a number of mRNAs that are potential targets of eIF5A regulation have been reported (Xu et al, 2004). Genetic studies using S. cerevisiae harboring eIF5A temperature-sensitive mutants suggest a direct or indirect role of eIF5A in cell wall integrity, mRNA decay, actin polarization, cell cycle progression and anti-apoptotic protection (Zuk and Jacobson, 1998;Valentini et al, 2002;Zanelli and Valentini, 2005;Chatterjee et al, 2006;Schrader et al, 2006). Future studies will be directed toward identification of eIF5A binding partners (proteins and mRNA) and understanding how downstream effector molecules are involved in the expression of these pleiotropic phenotypes in the temperature-sensitive eIF5A mutant strains.…”
Section: Discussionmentioning
confidence: 99%